Kualitas Pelayanan Terhadap Volume Penjualan pada SPBU Nusantara 44.53226 di Cilacap Utara - Tati Heryati; Rita Patonah; Dwi Linggarni (Universitas Indraprasta PGRI, 2022)
Sales Volume fluctuation is one of the problems that occur on the SPBU Nusantara 44.53226. The cause is suspected because of the poor quality of service provided by the gas station attendant to the customer. The purpose of this research is to: 1) Describe the quality of service (service quality); 2) Determine the sales volume of the product; 3) Analyze the influence of service quality on the volume of sales. This research uses a descriptive method with a quantitative approach. Data analysis techniques used the analysis of correlation, determination, and t-test. The results showed that: 1) The Quality of service in the company included in the high category; 2) the Volume of sales still experiences fluctuations; 3) There is no significant influence of service quality on the volume of sales at SPBU Nusantara 44.53226.